Differential Distribution of Retinal Ca2+/Calmodulin-Dependent Kinase II (CaMKII) Isoforms Indicates CaMKII-β and -δ as Specific Elements of Electrical Synapses Made of Connexin36 (Cx36) - Tetenborg, Stephan; Yadav, Shubhash C.; Hormuzdi, Sheriar G.; Monyer, Hannah; Janssen-Bienhold, Ulrike; Dedek, Karin (Frontiers in Molecular Neuroscience, 2017)
AII amacrine cells are essential interneurons of the primary rod pathway and transmit rod-driven signals to ON cone bipolar cells to enable scotopic vision. Gap junctions made of connexin36 (Cx36) mediate electrical coupling among AII cells and between AII cells and ON cone bipolar cells. These gap junctions underlie a remarkable degree of plasticity and are modulated by different signaling cascades. In particular, Ca2+/calmodulin-dependent protein kinase II (CaMKII) has been characterized as an important regulator of Cx36, capable of potentiating electrical coupling in AII cells. However, it is unclear which CaMKII isoform mediates this effect. To obtain a more detailed understanding of the isoform composition of CaMKII at retinal gap junctions, we analyzed the retinal distribution of all four CaMKII isoforms using confocal microscopy. These experiments revealed a differential distribution of CaMKII isoforms: CaMKII-α was strongly expressed in starburst amacrine cells, which are known to lack electrical coupling. CaMKII-β was abundant in OFF bipolar cells, which form electrical synapses in the outer and the inner retina. CaMKII-γ was diffusely distributed across the entire retina and could not be assigned to a specific cell type. CaMKII-δ labeling was evident in bipolar and AII amacrine cells, which contain the majority of Cx36-immunoreactive puncta in the inner retina. We double-labeled retinas for Cx36 and the four CaMKII isoforms and revealed that the composition of the CaMKII enzyme differs between gap junctions in the outer and the inner retina: in the outer retina, only CaMKII-β colocalized with Cx36-containing gap junctions, whereas in the inner retina, CaMKII-β and -δ colocalized with Cx36. This finding suggests that gap junctions in the inner and the outer retina may be regulated differently although they both contain the same connexin. Taken together, our study identifies CaMKII-β and -δ as Cx36-specific regulators in the mouse retina with CaMKII-δ regulating the primary rod pathway.